2014
DOI: 10.1080/09712119.2013.845103
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of aqueous extracts ofGenipa americanaL. (Rubiaceae) in inhibiting larval development and eclosion of gastrointestinal nematodes of sheep

Abstract: The anthelminthic efficacy in vitro of the aqueous extract of Genipa americana L. leaves was evaluated at final concentrations of 20, 30, 50, 75 and 100 mg (dry matter)/mL through egg hatching inhibition (EHI) tests and quantitative cultures. The observed lethal concentration LC 90 values for hatching and L3 development inhibition were 79.8 and 28.7 mg/mL, respectively. The extract was more effective in larval development inhibition (LDI) than in hatching inhibition. Phytochemical analysis revealed tannins and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Only our study identified flavonoids in leaves [ 24 ]. Furthermore, only one article described the presence of leucoanthocyanidins, catechins, and flavanones in the fruits of G. americana by HPLC analysis [ 28 ], and another study described its presence in fruits by colorimetric methods [ 13 ], demonstrating that the presence of flavonoids in leaf extract was not described previously.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Only our study identified flavonoids in leaves [ 24 ]. Furthermore, only one article described the presence of leucoanthocyanidins, catechins, and flavanones in the fruits of G. americana by HPLC analysis [ 28 ], and another study described its presence in fruits by colorimetric methods [ 13 ], demonstrating that the presence of flavonoids in leaf extract was not described previously.…”
Section: Resultsmentioning
confidence: 99%
“…In the study, a simple and effective procedure allowed the isolation of flavonoids from the leaves of G. americana . Previously only two papers described the detection of flavonoids in fruits [ 13 , 28 ] and one study published by our group identified these compounds in leaves [ 24 ] from G. americana . It is important to mention that this is a new phytochemical approach concerning the leaves of this species.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fruits are used to prepare beverages (Yee et al, 2010). Recently studies reported the utilization of G. americana as an anthelminthic in sheep (Nogueira et al, 2014).…”
Section: Introductionmentioning
confidence: 99%